Implementasi Program ABS-SBK oleh KAN dan MTsM Cupak Kabupaten Solok - Sari, Rani Novita; Nurman, Nurman; Fatmariza, Fatmariza; Ersya, Muhammad Prima (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2024)
This article examines the implementation of the Adat Basandi Syara’, Syara’ Basandi Kitabullah (ABS-SBK) by the Nagari Customs Body (KAN) and MTsM Cupak in Solok Regency. The program integrates several practices, including communal Dhuha and Zuhur prayers and the recitation and memorization of the Al-Qur’an. The research employs qualitative descriptive methods, with informants comprising the chairman and secretary of MTsM, students, the Wali Nagari, and traditional community leaders. Data collection was conducted through interviews and documentation. The findings indicate that the ABS-SBK program implemented by KAN and MTsM Cupak has been fairly successful. However, challenges remain, such as student participation in Zuhur prayers and limited funding for art activities. This initiative also plays a role in shaping students' character and contributing to the nation's intellectual development.